Moderation (wasatiyyah) in Islam and its manifestations from the Quran and Sunnah: Imam Bediuzzaman Said Nursi’s perspective - Fatah Yasin, Raudlotul Firdaus; Muflih, Betania Kartika; Zainan Nazri, Nurul Jannah; Muhamad Shukri, Abdul Salam (2017)
This work explores the ideas of Imam Nursi in identifying some manifestations of moderation in Islam. Employing library and textual analysis, it concludes that it is necessary to situate Imam Nursi’s tafsÊr,Rasail al-Nur,within the context of Tawhid framework, which constitutes the background of his entire system of thought. In general, this article points out that there are four most important manifestations of moderation in religious underpinnings: Islamic Faith, Worship, Ethics and Legislation. The study finds out several points, firstly, Islamic Faith stands in between two extremes; extreme excessiveness (the materialistic which abolishes the whole matter of metaphysical existence that cannot be proved by sensory evidence) and extreme deficiency (the unreserved associations or the unreserved belief in more than one god). Secondly, Islamic Worship presents a compromise between those who completely negate the divine side and those who devote all their teachings to worship part in seclusion from the practical productive daily life yet proposes a balance between worldly matters and religious concerns. Thirdly, Islamic Ethics reflects a balance between those who overestimate human nature thus think of it as pure good and those who underestimate it as pure evil. Finally, Islamic Legislation balances the individuals’ freedom with community interests and rights with responsibilities. Imam Nursi states that the purpose of a Muslim's life is to worship Allah and to devote oneself to seeking His love, in so doing, the middle path is to be applied. Imam Nursi advocates moderation and counsels abjuring limits, referring that to this hadith: “Too much or too little of anything is not good: moderation is the istiqamah, steadfastness”